Isotropic, high coercive field in melt-spun tetragonal Heusler Mn3Ge - Kalache, Adel; Kreiner, Guido; Ouardi, Siham; Selle, Susanne; Patzig, Christian; Hoeche, Thomas; Felser, Claudia (APL Materials, 2016)
Nanostructured Mn3Ge ribbons with a composition ranging from 77 to 74 at.% Mn were prepared using induction melting, melt-spinning, and subsequent heat treatment. The hard magnetic properties of the ribbons originate from the highly anisotropic tetragonal D022 structure of Mn3Ge. Depending on the composition and the amount of ferrimagnetic Mn5Ge2 as a secondary phase, a coercivity of up to μ0HC = 2.62 T was obtained for the Mn3Ge ribbons. Microstructure investigations by transmission electron microscopy confirmed the formation of the secondary phase. All samples show isotropic coercive fields, i.e., independent of the direction of the applied magnetic field in contrast to already known epitaxial thin films. The Curie temperature was found to be higher than 800 K, which is the temperature of the phase transition from the tetragonal D022 structure to the hexagonal D019 structure.
CRIS-Team Scopus Importer:2023-03-20